Sport and the New Culture of the 'Second Golden Age': Amsterdam's Sporting Entrepreneurs in the 1880s and 1890s. Issue 7 (24th May 2018) - Piercey, Nick
Abstract: In the second half of the nineteenth century, Amsterdam underwent important changes in its economic, social, and cultural life as the city entered what is often referred to as its 'Second Golden Age'. Old elites gave way to new and a new more entrepreneurial culture emerged focused on mass, visible, and consumable activities, including sport, in which the body played a central role. This was especially apparent from the late 1870s and 1880s when spatial changes within the city helped to ensure that sport was increasingly the location for new kinds of associational activity and the development of new products, all underpinned by the potential for profit. Entrepreneurs such as Perry & Co., De Gruyter, and the Amsterdamsche Sport-Club were able to effect strategic combinations between the new body culture and consumerism, producing a range of new products and exploiting new technologies to create new markets. In seizing these opportunities, Amsterdam's entrepreneurs were also reproducing the concept of the trainable, measurable, and consumable body.